Substrate- and temperature-controlled divergence in reactions of alcohols with TosMIC catalyzed by BF3 · Et2O: Facile access to sulfinates and sulfones. Issue 13 (3rd July 2017) - Pogaku, Naresh; Krishna, Palakodety Radha; Prapurna, Y. Lakshmi
ABSTRACT: An efficient BF3 · Et2 O-catalyzed divergent synthesis of sulfinate esters and sulfones through C–O and C–S bond formation has been achieved from alcohols and p -toluenesulfonylmethyl isocyanide (TosMIC). Various alcohols reacted smoothly with TosMIC under the present conditions at room temperature providing sulfinate esters exclusively. By tuning the reaction temperature, the alcohols that provide highly stabilized carbocation in the reaction medium afforded sulfones as sole products. This study was aimed at understanding the regioselectivity of ambidentate sulfinate ion and to elucidate the interpretation of sulfinate/sulfone scaffolds. GRAPHICAL ABSTRACT: